PEMANFAATAN AWIG-AWIG DALAM AKUNTABILITAS, TRANSPARASI, DAN PERAREM PENGELOLAAN KEUANGAN PADA KEARIFAN LOKAL MENYAMA BRAYA - Rai Dwi Andayani; Ni Luh Putu Widhiastuti (Jurnal Widya Akuntansi dan Keuangan, 2022)
In Balinese society, the function of financial management in Customary Village is very interesting to observe because in the function it is combined with elements of custom and tradition that develop in the Customary Village. This research was conducted to find out: 1) the implementation of awig-awig as the accountability control of financial management of Village, 2) the accountability process carried out by the administrators of Village. 3) the reason of collecting fee from pengampel (a customary villager who does not do his duty) when the village had received fund from the government,The result of the study showed that , 4) the role of awig-awig (Balinese Customary Regulation) in village financial management,5) implementation of local wisdom menyama braya in the daily action of the accountability principles and transparency in financial management. The result of the study showed that 1) ) awig-awig was used as a very effective control in supervising the administrators,2) in terms of accountability regarding the management process done by the traditional community administrators, the community fully entrusted the management to the traditional community administrators, 3) the collection fee was held because it was useful as a binder for the krama banjar (customary community), 4) the role of awig-awig in financial management was to support accountability, transparency, and community participation so that the income of Customary Village could increase more, 5) Accountability and transparency in financial management carried out by prajuru have been carried out as they should without leaving the meaning of local wisdom in menyama braya.